TransACT’s foundation and initial rollout: A memoir - Eckermann, Robin (Journal of Telecommunications and the Digital Economy, 2014)
TransACT (2000- ) introduced Australia’s first VDSL network, offering a ‘triple play’ of voice, data (e.g. Internet access), broadcast and video-on-demand services in Australia’s capital city, Canberra, in competition with the incumbent carrier Telstra. TransACT’s founding Chief Architect, Robin Eckermann, reminisces on the founding of TransACT and some of the lessons to be learned from this fore-runner of the National Broadband Network (NBN).